The Role of Pharmacotherapy and Psychotherapy in Borderline Personality Disorder - a literature review - Poloczek, Alicja; Szczerba, Jakub (Journal of Education, Health and Sport, 2024)
Borderline personality disorder (BPD) is a severe and heterogeneous psychiatric disorder known to begin at a young age, often in adolescence. It is associated with suicidal behaviour and self-harm. Up to 10 per cent of BPD patients die by suicide, so it is very important to find effective methods to alleviate the symptoms of this disorder [1]. A combination of psychotherapy and pharmacotherapy seems reasonable. An obstacle to widespread access to psychotherapy is the relatively high costs associated with the salaries of highly qualified psychotherapists. Another impediment is the long time required for effective psychotherapy and the frequent phenomenon of patients with unstable emotions discontinuing therapy prematurely. On the other hand, pharmacotherapy is necessary during periods of aggravation of the disorder, such as increased emotional lability, dysphoric states associated with aggression, impulsive behaviour and the presence of pseudopsychotic symptoms. This paper is a compilation of available treatments for borderline disorder. In the context of considering effective therapies for BPD, an important aspect is the need to increase the length of therapy and the availability of professional help for patients. In addition, research points to the benefits of combining psychotherapy with pharmacotherapy to more effectively alleviate the symptoms of this heterogeneous disorder. It is noteworthy that the relatively high cost of psychotherapy and the need to decrease.